2020
DOI: 10.1111/1365-2656.13365
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific plasticity across generations II: Grandpaternal effects are lineage specific and sex specific

Abstract: 1. Transgenerational plasticity (TGP) occurs when the environment encountered by one generation (F0) alters the phenotypes of one or more future generations (e.g. F1 and F2). Sex selective TGP, via specific lineages or to only male or female descendants, has been underexplored in natural systems, and may be adaptive if it allows past generations to fine-tune the phenotypes of future generations in response to sex-specific life-history strategies. 2. We sought to understand if exposing males to predation risk c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 66 publications
0
32
0
Order By: Relevance
“…Consequently, theoretical and empirical work seeking to understand the evolution of transgenerational plasticity would benefit from considering the conditions which influence sex‐specific patterns of transgenerational plasticity in both adaptive and non‐adaptive ways. Furthermore, given broad interest in understanding the consequences of transgenerational plasticity for future generations and its potential to influence adaptive evolution, future work should consider how sex‐specific effects in the first generation may alter the ways in which intergenerational effects persist for multiple generations in lineage‐specific and/or sex‐specific ways (Hellmann, Carlson, & Bell, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, theoretical and empirical work seeking to understand the evolution of transgenerational plasticity would benefit from considering the conditions which influence sex‐specific patterns of transgenerational plasticity in both adaptive and non‐adaptive ways. Furthermore, given broad interest in understanding the consequences of transgenerational plasticity for future generations and its potential to influence adaptive evolution, future work should consider how sex‐specific effects in the first generation may alter the ways in which intergenerational effects persist for multiple generations in lineage‐specific and/or sex‐specific ways (Hellmann, Carlson, & Bell, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating sex-specificity of transgenerational effects across a range of taxa have observed instances in which environmental modification such as dietary challenges, presence of predators, or behaviour-modifying drugs of the grandparental environment triggered sex-specific effects on grandoffspring phenotype. Intriguingly, in these cases, transgenerational effects tend to manifest in the opposite sex to that subjected to the grandparental treatment; that is, modification of the grandmaternal environment may enhance or inhibit trait expression among grandsons, or conversely, modification to the grandpaternal environment may enhance or inhibit trait expression among granddaughters 10,25,30,32,33 . Our findings are consistent with previous research, revealing opposing directions of sucrose-mediated grandmaternal effects in each of the sexes.…”
Section: Discussionmentioning
confidence: 99%
“…predation risk and levels of sexual conflict, among parents may catalyse transgenerational effects that differ in magnitude or direction across sexes, and which may also be lineage (genotype) specific 10 . Notwithstanding, currently it remains unclear whether such transgenerational effects are consistently instigated across diverse environmental stresses, whether they generally act to enhance or depress offspring performance, and whether they are transferred primarily through maternal or paternal lineages or hinge on interactions between both.…”
mentioning
confidence: 99%
“…While MPH treatment caused a significant effect in G 1 males but not G 1 females, this sex-specific effect was reversed in their progeny for one behavioural metric (CA1), with only female offspring and great-grandoffspring differing in behaviour based on their father’s/great-grandfather’s treatment. Other studies have observed transgenerational effects expressed in the sex opposite to the one originally affected by an environmental stimulus 33 37 . This result further emphasizes the importance of studying transgenerational effects in both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…First, many of these studies do not report potentially confounding effects of differences in survival or reproductive success between control and treatment lines. Second, some studies only investigate the effects in progeny of one sex, despite evidence that parental effects are sometimes sex-specific 33 37 . Third, most examples come from rodents (but see 5 , 14 , 27 , 37 ), which makes it unclear if these results can be generalized to other taxa.…”
Section: Introductionmentioning
confidence: 99%